2014
DOI: 10.1111/jfpp.12255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage, Oxygen and Concentration on the Levels of Key Volatiles in Processed Orange Juice

Abstract: Not from concentrate (NFC) and from concentrate (FC) commercially available orange juices were kept in storage for 8 weeks at 5C. One group of FC and NFC orange juice was stored with minimal headspace, whereas the other group was stored in the presence of oxygen. Weekly analysis of volatile concentrations in samples with selected ion flow tube mass spectrometry showed that most volatiles decreased over the period of the study. There were no significant differences in volatile concentrations between samples tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In total 16 aroma compounds were detected in the whole storage, while the content of most of these compounds declined after 15 days' storage. Similar results were also found in Ryo and Barringer's study that they found a majority of volatiles decreased significantly in the first week stored at 5°C because only the free and not bound aroma compounds can exist in the headspace and they could occur chemical reactions and oxidation (Ryo and Barringer 2015). Moshonas and Shaw found that the volatile compounds dropped dramatically in 9 weeks and the water-soluble volatiles lost 70%, while oil-soluble compounds lost 30% of the original concentration (Moshonas and Shaw 2000).…”
Section: Aroma Compoundssupporting
confidence: 89%
See 1 more Smart Citation
“…In total 16 aroma compounds were detected in the whole storage, while the content of most of these compounds declined after 15 days' storage. Similar results were also found in Ryo and Barringer's study that they found a majority of volatiles decreased significantly in the first week stored at 5°C because only the free and not bound aroma compounds can exist in the headspace and they could occur chemical reactions and oxidation (Ryo and Barringer 2015). Moshonas and Shaw found that the volatile compounds dropped dramatically in 9 weeks and the water-soluble volatiles lost 70%, while oil-soluble compounds lost 30% of the original concentration (Moshonas and Shaw 2000).…”
Section: Aroma Compoundssupporting
confidence: 89%
“…Moshonas and Shaw found that the volatile compounds dropped dramatically in 9 weeks and the water-soluble volatiles lost 70%, while oil-soluble compounds lost 30% of the original concentration (Moshonas and Shaw 2000). And Ryo and Barringer found that about 30% of oil and water-soluble volatiles were lost in the process (Ryo and Barringer 2015). The destruction of most orange juice volatiles is proposed to be the cause of an acidcatalyzed reaction (Petersen et al 1998;Berlinet et al 2005).…”
Section: Aroma Compoundsmentioning
confidence: 99%
“…There is only one study on a beverage other than coffee. This investigation reported the effects of storage, oxygen, and concentration method on the levels of key volatiles in orange juice . Not from concentrate (NFC) and from concentrate (FC) commercially available orange juices were kept in storage for 8 weeks at 5 °C, with one group of juices stored with minimal headspace, and the other group stored in the presence of oxygen.…”
Section: Current Applications Of Sift‐ms In Food Aroma Analysismentioning
confidence: 99%
“…This investigation reported the effects of storage, oxygen, and concentration method on the levels of key volatiles in orange juice. 83 Not from concentrate (NFC) and from concentrate (FC) commercially available orange juices were kept in storage for 8 weeks at 5 °C, with one group of juices stored with minimal headspace, and the other group stored in the presence of oxygen. Most volatiles decreased over the period of the study, with no significant differences in volatile concentrations between samples that were exposed to the different levels of oxygen.…”
Section: Concentrations Of Seven Importantmentioning
confidence: 99%